What good are interviews for thinking about culture? Demystifying interpretive analysis - Pugh, Allison J (American journal of cultural sociology, 2013)
This article evaluates the claims of a small but active group of culture scholars who have used theoretical models of bifurcated consciousness to allege important methodological implications for research in culture. These scholars, whom I dub ‘cognitive culturalists’, have dismissed the utility of in-depth interviewing to access the visceral, causally powerful level of ‘practical consciousness’. I argue these scholars are misguided in their diagnosis of a problem (interviews can only access people's after-the-fact rationalizations), and their vision of a solution (culture scholars need to access the ‘snap judgments’ that map onto the subterranean level of practical consciousness). I contend these flaws are tied to a limited understanding of the kind of information available in interviews, particularly the in-depth interview subjected to interpretive analysis. Using data from a recent book project on commitment, I elaborate on four kinds of information harbored in interviews: the honorable, the schematic, the visceral and meta-feelings. I rely on these forms of data to argue for scholars to expect, and to use analytically – rather than strive to ‘solve’ theoretically – the contradictory cultural accounts that our research subjects evince. Furthermore, I demonstrate how interpretive interviewing allows researchers access to an emotional landscape that brings a broader, social dimension to individual motivation.